Mycobacterium genavense infection in two species of captive snakes. Issue 1 (December 2016) - Ullmann, Leila; das Neves Dias-Neto, Ramiro; Cagnini, Didier; Yamatogi, Ricardo; Oliveira-Filho, Jose; Nemer, Viviane; Teixeira, Rodrigo; Biondo, Alexander; Araújo, João
Abstract Background Mycobacterium is an important zoonotic agent with companion, livestock and wildlife animals reportedly playing a role as reservoirs. Although its association with reptiles has been described, the disease cycle remains to be fully established, particularly in snakes. Accordingly, this study aimed to report the occurrence of mycobacteriosis with clinical pneumonia in one exotic python snake (Python molurus ) and one native green snake (Philodryas olfersii ) from the Sorocaba Zoo, São Paulo state, Brazil. Methods Diagnosis was based on necropsy, histopathological examination, Ziehl-Neelsen stain and immunohistochemistry. Results Using a nested PCR followed by DNA sequencing and bioinformatics analysis, the causativeMycobacterium species was identified asMycobacterium genavense . Conclusion Mycobacterium genavense is an infectious zoonotic agent of animal and public health concerns.